Model Pendekatan Education of the Mother Community (EMC) dalam Pencegahan Diare pada Anak di Pekapuran Raya - Sri Herlina (Jurnal Kesehatan Islam : Islamic Health Journal, 2018)
AbstractMorbidity of diarrhea diseases in developing countries is a public healthconcern because the prevalence is still high particularly for children under five years. 207 children recorded had the diarrhea in Pekapuran Raya.This study aims to know the benefits of model approach of education of the mother community (EMC), particularly to the mother'sknowledge on prevention of diarrhea. Quasi-experimental research design one group pre-post test design conducted on 38 mother that have children under five years in Pekapuran Raya Subdistrict of Banjarmasin. The results of pre-test and post-test shows that there is understanding increased the mothers for prevention of diarrhea afterpromotion using model approach of education of the mother community(p <0,05). This model proven to be useful for deliver the healthy information concerning prevention of diarrhea for children. Keywords:diarrhea, prevention, model, education of the mother community (EMC)